Evaluating the effect of plastomer modified asphalt mixture on high/low temperature performance - Ullah, Rafi; Hafeez, Imran; Haroon, Waqas; Haider, Safeer (Mehran University research journal of engineering and technology, 2021)
Asphalt pavement's surfaces deteriorate over time due to combined effect of traffic and surrounding environment. Fatigue and rutting are the major distresses which cause failures in flexible pavements. Different temperature control computer operated equipment's are being used worldwide to predict the performance of asphalt mixtures at approximately same condition to those in-service pavements. Similarly, different types of polymers such as elastomer and thermoplastic have been used all over the world in Hot Mix Asphalt (HMA) for the improvement of asphalt mixtures. But little attention has been taken to evaluate the effect of plastomer on hot mix asphalt performance. Moreover, the initial cost of elastomer is higher than other types of polymers such as plastomer. The aim of this research study is to check the effect of various plastomers on high/low temperature performance of asphalt mixture. Four performance tests like Cooper wheel tracker, dynamic modulus, uniaxial repeated load and four-point bending beam test are used to evaluate the effect of different type of plastomers such as polyethylene terephthalate, high density and low density polyethylene with limestone aggregate quarry and 60/70 pen grade asphalt binder. This research study concludes that plastomer increases flexibility and hardness of asphalt mixtures and improves the rut resistance, dynamic modulus and fatigue life of asphalt mixtures. Plastomer modification shows significant benefits as compared to neat binder for high/low temperature performance. Moreover, it can be concluded that plastomer provides an efficient and economical blend of asphalt mixture.